Differential diagnosis of IgG4-related sialadenitis, primary Sjögren syndrome, and chronic obstructive submandibular sialadenitis. Issue 2 (February 2017) - Hong, X.; Li, W.; Xie, X.-Y.; Zhang, Z.-Y.; Chen, Y.; Gao, Y.; Peng, X.; Su, J.-Z.; Zhang, Y.-Y.; Wang, Z.; Cai, Z.-G.; Zhang, L.; et al.
Abstract: Our aim was to differentiate IgG4-related sialadenitis, primary Sjögren syndrome, and chronic obstructive submandibular sialadenitis by analysing clinical, radiographic, and pathological features. Fifty-five patients, 50, and 50 were enrolled, respectively and their baseline characteristics and serological, sialographic, and pathological findings compared. The male:female ratio for IgG4-related sialadenitis was 1:1.2 for primary Sjögren syndrome 1:15.7, and for chronic obstructive submandibular sialadenitis1:0.92. Numbers with enlarged salivary glands were 55, 16, and 50; with xerostomia 26, 48, and 0; with a history of allergy 26, 4, and 6, and with coexisting systemic disease 12, 19, and 0 (p = 0.14). Mean (SD) serum IgG4 concentrations were 109.1 (97.9), 4.9. (1.9) g/L, and 5.3 (1.6) g/L, p < 0.001 in all cases. Sialography showed enlargement of the gland, dilatation of the duct, and slightly decreased secretory function in IgG4-related disease; obvious sialectasia and decreased secretory function in Sjögren syndrome; and dilatation of Wharton's duct and filling defects in obstructive sialadenitis. Histopathological examination showed lymphoplasmacytic infiltration with storiform fibrosis, lymphoplasmacytic inflammation and lymphoepithelial lesions, and dilatation of the duct with epithelial metaplasia in the three groups, respectively. The number of IgG4-positive plasma cells was 123 (45)/HPF, 8 (3)/HPF, and 5 (4)/HPF, while the IgG4-/IgG-positive cell ratio was 71.7 (13.9)%, 4.6 (2.5)%, 18.9 (19.7)%, respectively (p < 0.001). The three conditions have different clinical, radiographic, and pathological features that provide important clues to the differential diagnosis. Serological and histological tests are important, and comprehensive consideration is necessary.